2020
DOI: 10.1186/s13071-020-04410-w
|View full text |Cite
|
Sign up to set email alerts
|

Facial cleanliness indicators by time of day: results of a cross-sectional trachoma prevalence survey in Senegal

Abstract: Background The World Health Organization-recommended strategy for trachoma elimination as a public health problem is known by the acronym “SAFE”, where “F” stands for facial cleanliness to reduce transmission of ocular Chlamydia trachomatis infection. Accurately and reliably measuring facial cleanliness is problematic. Various indicators for measuring an unclean face exist, however, the accuracy and reliability of these indicators is questionable and their relationship to face washing practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Our use of nearby face-washing water likely dampened associations in this analysis. Future studies may be informative as on-plot water availability increases in these communities [ 26 , 27 ]. Second, our hypothetical intervention randomly allocated exposures at cluster and household levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our use of nearby face-washing water likely dampened associations in this analysis. Future studies may be informative as on-plot water availability increases in these communities [ 26 , 27 ]. Second, our hypothetical intervention randomly allocated exposures at cluster and household levels.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we provide an approach that frames flexible multilevel models in terms of interpretable, population-level associations. As with any data analysis, to infer causality, we must assume (among other things) that the identifiability conditions of consistency and conditional exchangeability with positivity are met [ 27 ]. Above, using language geared toward readers less familiar with causal inference terminology, we allude to a potential violation of consistency.…”
Section: Discussionmentioning
confidence: 99%
“…In Senegal, 1613 children, less than 9 years, were assessed by questionnaires for facial cleanliness in order to determine factors to reduce infection rates of the eye. It was noted that a high number of children did not have clean faces throughout the day [17]. In order for the SAFE strategy to be successful, it needs to rely on the continued support and coordination of a number of contributors, including local governments of endemic areas, manufacturers of azithromycin, and the WHO [5,18].…”
Section: Treatment -Managementmentioning
confidence: 99%
“…The time of day when clean face was documented also varied as survey teams began at one house and moved throughout the village throughout the day. Other studies have shown that time of day and physical location of data collection may impact the likelihood of a face being clean [23][24][25].…”
Section: Programmatic Achievementsmentioning
confidence: 99%